Eugenik Dalam Era Genetik - Kusmaryanto, C.B. (Jurnal Orientasi Baru, 2006)
The word eugenic comes from Greek words eu + genes (eugenes) which means wellborn or good in birth. Although the word eugenics was coined only in 1883 by Francis Galtom, the practice of eugenics dated back at least to Plato. It reached its peak in the filst half of 20th century, especially during Hitler's time. Hitler tried to purify Arian race by eliminating Jews, homosexual person, hippies, handicapped person etc. From that time on, the word eugenics has a negative connotation. Unfortunately, eugenics was reborn in our time where the technological developments grow rapidly. Eugenic reemerges in various new forms and various situations such as abortion, assisted reproduction, pre natal diagnostic, cloning, genetic engineering and genomic mapping. The problems of eugenic relate mainly to justice, equality between genders, definition of good - bad and above all it relates with the basic human right to live.